(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The study was conducted to determine the effects of dietary premix on growth and reproductive performance of Yankasa ewes on confined pen. The design of the experiment used was Complete Randomized Design (CRD), whereby twenty-five (25) Yankasa lambs were randomly allocated to five (5) treatment groups comprising of five animals per treatment. The animals were randomized by their weights and placed into their groups fed basal diets, and 4 levels of industrially and locally compounded premix. 1 kg of the basal feed were given on daily basis (5 % of the ewe’s body weight) throughout the period. Dietary premix was administered in feed to the animals at 4 inclusion levels (0.25, 0.50, 0.75 and 1.) with clean water provided ad-libitum in the morning in a confined environment; the feed offered and left over were recorded daily. The sheep were weighed at the beginning of the study and were-weighed weekly. The findings of this study showed that dietary treatments had effect (P<0.05) on final weight, total weight gain and feed conversion ratio. However, the average daily weight gain, total feed intake and average daily feed intake were not significantly affected (P>0.05) by the dietary treatments. The results also showed that as the premix supplementation increases in the diet, the final and total weight gain increases. The Feed conversion ratio (FCR) results in T5 differs significantly from those in T1 and T2 but statistically the same with those in T3 and T4. However, animals on T5 (14.86) had better (P<0.05) feed conversion ratio compare to those on T2 and T1>